2019
DOI: 10.3389/feduc.2019.00086
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial Continuity Effect vs. Spatial Contiguity Failure. Revising the Effects of Spatial Proximity Between Related and Unrelated Representations

Abstract: The split-attention effect refers to learning with related representations in multimedia. Spatial proximity and integration of these representations are crucial for learning processes. The influence of varying amounts of proximity between related and unrelated information has not yet been specified. In two experiments (N 1 = 98; N 2 = 85), spatial proximity between a pictorial presentation and text labels was manipulated (high vs. medium vs. low). Additionally, in Experiment 1, a control group with separated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Nevertheless, the result indicate that the spatial distance of picture elements matters with regard to the perceptual linkage of information. With the results for one of the two paintings, the present study confirms prior research about the spatial contiguity effect on perceptual ( 14 , 15 ) and cognitive linkage ( 4 , 11 , 12 , 13 ), and doing so, used the measure of backward fixation counts, which to our knowledge is used rather seldom (e.g. 30 ) Furthermore, the present study expands prior research about the spatial contiguity effect from multimedia research often examining text-picture relations in the field of natural science to processing related pairs of picture elements in the field of art reception ( 8 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, the result indicate that the spatial distance of picture elements matters with regard to the perceptual linkage of information. With the results for one of the two paintings, the present study confirms prior research about the spatial contiguity effect on perceptual ( 14 , 15 ) and cognitive linkage ( 4 , 11 , 12 , 13 ), and doing so, used the measure of backward fixation counts, which to our knowledge is used rather seldom (e.g. 30 ) Furthermore, the present study expands prior research about the spatial contiguity effect from multimedia research often examining text-picture relations in the field of natural science to processing related pairs of picture elements in the field of art reception ( 8 ).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, research on the spatial contiguity failure indicates that the influence of spatial contiguity on perceptual and cognitive linkage is independent of the semantic relation of the picture elements. Beege, Wirzberger, Nebel, Schneider, Schmidt, and Rey (2019) varied the spatial distance between a pictorial presentation and related text labels (high vs. medium vs. low) and could show that retention and transfer performance was best with medium distance. Beege et al (2019) argue that presenting labels too close to the related picture content leads also to a higher proximity between unrelated text and picture elements, hindering cognitive integration processes for related information.…”
Section: Spatial Distance Between Related Picture Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of interface design violates a contiguity principle generating an extraneous sensory memory load further leading to working memory overload (Clark and Mayer 2016;Makransky et al 2019). The harmful consequences of this design can be explained by the law of proximity referring to a phenomenon fostering learning when related representations are spatially integrated or close to each other (Beege et al 2019;Clark and Mayer 2016). With regard to surveys is shown that when items are presented in proximity to each other, the likelihood for an assimilation effect increases (Couper et al 2001;Tourangeau et al 2013).…”
Section: Cognitivementioning
confidence: 99%
“…For example, based on research on generative activities and its relation to monitoring accuracy (e.g., Prinz et al, 2020;van Gog et al, 2020), it may be assumed that effort and load within active integration affect metacomprehension judgments rather indirectly via comprehension rather than directly (without relating to comprehension). With regard to split attention, one may assume that a possible effort-metacomprehensionrelationship may not be mediated by comprehension as the effort-comprehension relationship may be hampered by investing effort in overcoming the split-attention rather than germane learning activities (e.g., Beege and Colleagues, 2019). However, as the research basis for these assumptions is not yet solid enough to form distinct hypotheses (apart from the direction of the general relationship between perceived mental load or effort and metacomprehension judgments), we chose a more exploratory approach to take a first step towards understanding how (perceived) mental load and mental effort are related to metacognitive monitoring of learning under varying conditions of multimedia design.…”
Section: Introductionmentioning
confidence: 99%